GW190521: a binary black hole merger inside an active galactic nucleus? - Morton, Sophia; Rinaldi, Stefano; Torres-Orjuela, Alejandro; Derdzinski, Andrea; Vaccaro, Maria; Del Pozzo, Walter (Physical review, 2023)
GW190521, the most massive binary black hole merger confidently detected by the LIGO-Virgo-KAGRA Collaboration, is the first gravitational-wave observation of an intermediate-mass black hole. The signal was followed approximately 34 days later by flare ZTF19abanrhr, detected in AGN J⁢124942.3+344929 by the Zwicky Transient Facility at the 78% spatial contour for GW190521’s sky localization. Using the GWTC-2.1 data release, we find that the association between GW190521 and flare ZTF19abanrhr as its electromagnetic counterpart is preferred over a random coincidence of the two transients with a log Bayes’ factor of 8.6, corresponding to an odds ratio of ∼5400 :1 for equal prior odds and ∼400 :1 assuming an astrophysical prior odds of 1/13. Given the association, the multimessenger signal allows for an estimation of the Hubble constant, finding 𝐻0=10⁢2+27−25 km s−1 Mpc−1 when solely analyzing GW190521 and 79.2+17.6−9.6 km s−1 Mpc−1 assuming prior information from the binary neutron star merger GW170817, both consistent with the existing literature.